Positive electrode active material and lithium secondary battery containing them
Patent Information
- Application Number
- JP2024229588
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-10-26
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-10-24
AI Technical Summary
【0039】 前述したように、正極活物質に含まれるリチウム複合酸化物は、充放電時にリチウム複合酸化物に対するリチウムイオンのインターカレーション/デインターカレーションによって体積変化を必然的に伴うしかない。このとき、充放電時のリチウム複合酸化物の体積変化を緩和させるか、または体積変化による応力発生を最小化して粒子の損傷を防止できる方案は、種々存在できるが、未だ正極活物質に含まれるリチウム複合酸化物の損傷に起因するリチウム二次電池の劣化問題は、十分に解消されたとは見なし難い。
Smart Images

Figure 2025036592000001 
Figure 2025036592000002 
Figure 2025036592000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode active material and a lithium secondary battery including the same, and more specifically, to a positive electrode active material including a lithium composite oxide containing at least nickel and cobalt, in which the cobalt in the lithium composite oxide has a concentration gradient with at least a different gradient from the surface portion to the center portion, thereby enabling improvement in particle stability not only in the surface portion of the lithium composite oxide but also in the center portion, a positive electrode including the positive electrode active material, and a lithium secondary battery using the positive electrode. [Background technology]
[0002] Batteries store electricity by using materials capable of electrochemical reactions at the positive and negative electrodes. A representative example of such batteries is a lithium secondary battery, which stores electrical energy by the difference in chemical potential when lithium ions are intercalated / deintercalated at the positive and negative electrodes.
[0003] The lithium secondary battery is manufactured by using a material capable of reversible intercalation / deintercalation of lithium ions as a positive electrode and a negative electrode active material, and filling an organic electrolyte or a polymer electrolyte between the positive electrode and the negative electrode.
[0004] Lithium composite oxides are used as the positive electrode active material of lithium secondary batteries, and examples of such composite oxides that have been researched include LiCoO2, LiMn2O4, LiNiO2, and LiMnO2.
[0005] Among the positive electrode active materials, LiCoO2 is the most widely used due to its excellent life characteristics and charge / discharge efficiency. However, it has a drawback in that it is expensive due to the limited availability of cobalt as a raw material, and thus has limited price competitiveness.
[0006] Lithium manganese oxides such as LiMnO2 and LiMn2O4 have the advantages of being thermally safe and inexpensive, but have problems with small capacity and poor high-temperature properties. In addition, LiNiO2-based positive electrode active materials show high discharge capacity battery characteristics, but are difficult to synthesize due to the problem of cation mixing between Li and transition metals, which causes major problems in rate characteristics.
[0007] In addition, a large amount of Li by-products are generated depending on the degree of cation mixing, and most of these Li by-products consist of compounds of LiOH and Li2CO3, which cause gelation during the manufacture of the positive electrode paste and gas generation with the progress of charge and discharge after the electrode is manufactured. Residual Li2CO3 not only increases the swelling phenomenon of the cell, reducing the cycle, but also causes the battery to swell.
[0008] Meanwhile, the lithium composite oxide contained in the positive electrode active material undergoes volume changes due to the intercalation / deintercalation of lithium ions into the lithium composite oxide during charging and discharging. Normally, lithium composite oxide is in the form of secondary particles formed by agglomeration of multiple primary particles, but if a sudden volume change occurs in the primary particles during charging and discharging, or if stress accumulates due to repeated charging and discharging, problems arise in that cracks occur in the secondary particles, or the crystal structure collapses or changes in the crystal structure (phase transition) occur.
[0009] These problems ultimately act as a cause of reduced stability and reliability of the positive electrode active material, and therefore various studies are being conducted to alleviate the volume change of the lithium composite oxide during charging and discharging, or to minimize the generation of stress due to the volume change, thereby preventing damage to the particles. Summary of the Invention [Problem to be solved by the invention]
[0010] In the lithium secondary battery market, the growth of lithium secondary batteries for electric vehicles is playing a leading role, while the demand for cathode materials used in lithium secondary batteries is also continuously changing.
[0011] For example, lithium secondary batteries using LFP have traditionally been used primarily for safety reasons, but in recent years there has been a trend toward the widespread use of nickel-based lithium composite oxides, which have a larger energy capacity per weight than LFP.
[0012] As a result, the positive electrode active material used in higher specification lithium secondary batteries must adequately meet all of the expected stability and reliability even under more severe operating conditions.
[0013] In the past, in order to alleviate the volume change of the lithium composite oxide during charging and discharging or to minimize the generation of stress due to the volume change and prevent damage to the particles, the degree of aggregation of the primary particles was intentionally reduced to create a certain amount of voids between the primary particles, thereby dispersing the stress due to the volume change of the primary particles. However, such lithium composite oxides have a limitation in that they have a low energy density per unit volume.
[0014] Under such circumstances, the present inventors have clarified that when cobalt in a lithium composite oxide containing at least nickel and cobalt has a concentration gradient with at least a different gradient from the surface portion to the center portion, the stability of particles in the lithium composite oxide can be improved not only in the surface portion but also in the center portion.
[0015] Accordingly, the present invention aims to provide a positive electrode active material comprising a lithium composite oxide containing at least nickel and cobalt, in which cobalt in the lithium composite oxide has a concentration gradient that decreases from the surface portion toward the center portion of the lithium composite oxide, the concentration gradient of the cobalt having at least different slopes, and the signs of the different slopes are the same.
[0016] The present invention also provides a cathode active material including a lithium composite oxide which is a secondary particle formed by agglomeration of a plurality of primary particles, and in which a coating layer is formed to cover at least a portion of the interfaces between the primary particles and the surfaces of the secondary particles, wherein cobalt in the lithium composite oxide has a concentration gradient which decreases from the surface portion to the center portion of the lithium composite oxide, the concentration gradients of the cobalt having at least different gradients, and the different gradients have the same signs.
[0017] Another object of the present invention is to provide a positive electrode comprising the positive electrode active material defined herein.
[0018] It is yet another object of the present invention to provide a lithium secondary battery using the positive electrode defined herein. [Means for solving the problem]
[0019] According to one aspect of the present invention, there is provided a positive electrode active material including a lithium composite oxide containing at least nickel and cobalt, in which cobalt in the lithium composite oxide has a concentration gradient that decreases from a surface portion toward a center portion of the lithium composite oxide, and the concentration gradient of the cobalt has at least a heterogeneous gradient.
[0020] The concentration gradient of the cobalt present in the lithium composite oxide has at least different gradients, and the signs of the different gradients are the same. That is, the cobalt present in the lithium composite oxide decreases in the same direction in the region where the different gradients exist, but the extent of the decrease in the concentration is different.
[0021] In an embodiment, the absolute value of the gradient of the cobalt in the lithium composite oxide relatively close to a surface portion of the lithium composite oxide may be greater than the absolute value of the gradient of the cobalt relatively close to a center portion of the lithium composite oxide.
[0022] In one embodiment, when an EP-EDS (Energy Profiling-Energy Dispersive X-Ray Spectroscopy) analysis is performed to measure a cumulative concentration of cobalt from the surface of the secondary particles to a depth penetrated by the electron beam using an electron beam irradiated at an acceleration voltage increasing from 1 kV to 30 kV to the surface of the lithium composite oxide, an inflection point at which the slope of the concentration gradient of the cobalt in the lithium composite oxide changes may be present within a region of an acceleration voltage of 7.5 kV to 12.5 kV.
[0023] The lithium composite oxide is a secondary particle formed by agglomeration of a plurality of primary particles, and the cobalt in the secondary particles can have a concentration gradient that decreases from the surface portion toward the center portion of the secondary particles.
[0024] In this case, during an EP-EDS (Energy Profiling-Energy Dispersive X-Ray Spectroscopy) analysis in which an electron beam is irradiated onto the surface of the secondary particles at an accelerating voltage that increases from 1 kV to 30 kV to measure a cumulative concentration of cobalt from the surface of the secondary particles to a depth penetrated by the electron beam, an inflection point at which the gradient of the concentration of cobalt in the secondary particles changes may exist within a region in which the accelerating voltage is 7.5 kV to 12.5 kV.
[0025] In one embodiment, when the gradient of the concentration of the cobalt in the lithium composite oxide in the region of the acceleration voltage of 1 kV to 10 kV is s1, the gradient of the concentration of the cobalt in the lithium composite oxide in the region of the acceleration voltage of 1 kV to 10 kV can satisfy the following formula 1.
[0026] [Formula 1] 2.0≦s1≦3.6
[0027] Furthermore, when the gradient of the concentration of the cobalt in the lithium composite oxide in the region where the acceleration voltage is 10 kV to 30 kV is s2, the gradient of the concentration of the cobalt in the lithium composite oxide in the region where the acceleration voltage is 10 kV to 30 kV can satisfy the following formula 2.
[0028] [Formula 2] 0.2≦s2≦0.7
[0029] Preferably, when a gradient of the concentration gradient of the cobalt in the lithium composite oxide in an acceleration voltage range of 1 kV to 10 kV is s1 and a gradient of the concentration gradient of the cobalt in the lithium composite oxide in an acceleration voltage range of 10 kV to 30 kV is s2, the s1 and s2 can satisfy the following formula 3.
[0030] [Formula 3] 1.7≦s1-s2≦3.0
[0031] In one embodiment, the lithium composite oxide is represented by the following formula 1.
[0032] [C1] Li w Ni 1-(x+y+z+z’) Co x M1 y M2 z B z’ O2
[0033] (where: M1 is at least one selected from Mn and Al; M2 is at least one selected from P, Sr, Ba, Ti, Zr, Mn, Al, W, Ce, Hf, Ta, Cr, F, Mg, Cr, V, Fe, Zn, Si, Y, Ga, Sn, Mo, Ge, Nd, Gd, and Cu; M1 and M2 are different from each other, 0.5≦w≦1.5, 0≦x≦0.50, 0≦y≦0.20, 0≦z≦0.20, 0≦z'≦0.20.
[0034] The lithium composite oxide may further include a coating layer covering at least a part of the interfaces between the primary particles and the surfaces of the secondary particles, and in this case, the coating layer may contain at least one metal oxide represented by the following Chemical Formula 2.
[0035] [Case 2] Li a M3 b O c
[0036] (where: M3 is at least one selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, B, P, Eu, Sm, W, Ce, V, Ba, Ta, Sn, Hf, Ce, Gd, and Nd, and 0≦a≦10, 0≦b≦8, 2≦c≦13, except for the case where a and b are both 0.
[0037] According to another aspect of the present invention, there is provided a positive electrode comprising the positive electrode active material defined herein.
[0038] According to yet another aspect of the present invention, there is provided a lithium secondary battery using the positive electrode defined herein. Effect of the Invention
[0039] As described above, the lithium composite oxide contained in the positive electrode active material inevitably undergoes volume change due to the intercalation / deintercalation of lithium ions into the lithium composite oxide during charging / discharging. Although there are various methods for reducing the volume change of the lithium composite oxide during charging / discharging or minimizing the stress caused by the volume change to prevent damage to the particles, it is difficult to say that the problem of deterioration of lithium secondary batteries caused by damage to the lithium composite oxide contained in the positive electrode active material has been sufficiently solved.
[0040] However, according to the present invention, in a lithium composite oxide containing at least nickel and cobalt, when the cobalt in the lithium composite oxide has a concentration gradient that decreases from the surface portion to the center portion of the lithium composite oxide and the concentration gradients of the cobalt have at least different slopes with the same sign, problems such as the occurrence of cracks in secondary particles, the collapse of the crystal structure, or the change in the crystal structure (phase transition) despite repeated charging and discharging can be improved.
[0041] As a result, when the positive electrode active material according to the present invention is used, it becomes possible to delay the performance deterioration of the lithium secondary battery caused by the positive electrode active material.
[0042] In addition to the above-mentioned advantages, specific advantages of the present invention will be described below together with specific matters for carrying out the invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0043] Hereinafter, the positive electrode active material according to the present invention and the lithium secondary battery including the positive electrode active material will be described in more detail.
[0044] positive electrode active material According to one aspect of the present invention, there is provided a positive electrode active material comprising a lithium composite oxide containing at least nickel and cobalt. The lithium composite oxide is a composite metal oxide that contains lithium in addition to nickel and cobalt and is capable of intercalating and deintercalating lithium ions.
[0045] Cobalt in the lithium composite oxide may have a concentration gradient that decreases from the surface to the center of the lithium composite oxide. The concentration of the transition metal in the lithium composite oxide may be measured by various known methods. For example, after cross-section processing of the lithium composite oxide, the concentration of the target transition metal may be analyzed by line scanning through EDS mapping. In this case, the change in the concentration of the target transition metal in the direction from the surface to the center of the lithium composite oxide may be confirmed. In addition, the accelerating voltage (V acc ) is changed, and the concentration of the target transition metal accumulated from the surface of the lithium composite oxide to a specific depth penetrated by the electron beam according to the accelerating voltage is measured. -ray Spectroscopy (EP-EDS) method.
[0046] In the present application, the concentration of transition metals was analyzed by the above-mentioned EP-EDS method. Specifically, in the EP-EDS (Energy Profiling-Energy Dispersive X-Ray Spectroscopy) analysis, which measures the cumulative concentration of cobalt from the surface of the secondary particles to the depth penetrated by the electron beam using an electron beam irradiated at an accelerating voltage increasing from 1 kV to 30 kV to the surface of the lithium composite oxide according to the present application, the lithium composite oxide shows a concentration gradient in which the concentration of cobalt decreases from the surface to the center.
[0047] For example, when the surface of the lithium composite oxide is irradiated with an electron beam having an accelerating voltage of 10 kV and the electron beam can penetrate to a depth of about 300 nm from the surface of the lithium composite oxide, the concentration of the target transition metal present in a region 300 nm deep from the surface of the lithium composite oxide can be measured by the EP-EDS analysis. Also, when the surface of the lithium composite oxide is irradiated with an electron beam having an accelerating voltage of 20 kV and the electron beam can penetrate to a depth of about 800 nm from the surface of the lithium composite oxide, the concentration of the target transition metal present in a region 800 nm deep from the surface of the lithium composite oxide can be measured by the EP-EDS analysis.
[0048] That is, when the cumulative concentration of the target transition metal measured decreases as the acceleration voltage of the electron beam irradiated to the surface of the lithium composite oxide increases, it can be interpreted that the concentration of the target transition metal has a decreasing gradient from the surface portion to the center portion of the lithium composite oxide.
[0049] In this case, the cobalt concentration gradient may be such that the cobalt concentration decreases continuously or discontinuously from the surface portion to the center portion of the lithium composite oxide.
[0050] In other words, when the concentration of cobalt decreases from the start point to the end point within any interval in which the concentration of the cobalt is measured, it can be said that the cobalt has a concentration gradient that decreases from the start point to the end point within the any interval.
[0051] In addition, the concentration gradient of cobalt in the lithium composite oxide may have at least different gradients, i.e., there may be a plurality of concentration gradient sections having different gradients from each other in the direction from the surface portion to the center portion of the lithium composite oxide.
[0052] In this case, the heterogeneous gradients of the concentration gradient of cobalt in the lithium composite oxide means that there are heterogeneous gradients with significant differences. That is, the heterogeneous gradients indicate differences outside the error range, preferably 2x or more, more preferably 3x or more. For example, when any one of the heterogeneous gradients has a gradient of x, the other gradient is preferably 2x or more, more preferably 3x or more, and it can be considered that there are heterogeneous gradients as defined in the present application.
[0053] If a concentration gradient section that is closest to the outermost periphery of the lithium composite oxide is defined as a first concentration gradient section, and a concentration gradient section that is inside the first concentration gradient section is defined as a second concentration gradient section, the slope of the cobalt concentration gradient in the first concentration gradient section and the slope of the cobalt concentration gradient in the second concentration gradient section are independent of each other and have the same sign.
[0054] Meanwhile, when the concentration of the transition metal in the lithium composite oxide is analyzed by the above-mentioned EP-EDS method, the absolute value of the slope of the cobalt in the lithium composite oxide relatively closer to the surface of the lithium composite oxide may be greater than the absolute value of the slope of the cobalt relatively closer to the center of the lithium composite oxide.
[0055] According to the above example, the absolute value of the slope of the cobalt concentration gradient in the first concentration gradient section is greater than the absolute value of the slope of the cobalt concentration gradient in the second concentration gradient section.
[0056] That is, the decrease in the cobalt concentration is relatively large in a region relatively close to the surface of the lithium composite oxide, and the decrease in the cobalt concentration is relatively small in a region relatively close to the center of the lithium composite oxide.
[0057] In this manner, the first concentration gradient section and the second concentration gradient section, in which the absolute value of the slope of the cobalt concentration gradient is different from each other, are formed from the surface section to the center of the lithium composite oxide, where intercalation / deintercalation of lithium ions is relatively concentrated, so that the particle stability can be improved in the surface section of the lithium composite oxide, and the particle stability can be improved not only in the surface section but also in the center of the lithium composite oxide by mitigating the decrease in cobalt in the second concentration gradient section.
[0058] Specifically, in an EP-EDS (Energy Profiling-Energy Dispersive X-Ray Spectroscopy) analysis in which an electron beam is irradiated onto a surface of the lithium composite oxide at an accelerating voltage that increases from 1 kV to 30 kV to measure a cumulative concentration of cobalt from the surface of the secondary particles to a depth penetrated by the electron beam, an inflection point at which the gradient of the concentration of cobalt in the lithium composite oxide changes may be present within a region of an accelerating voltage of 7.5 kV to 12.5 kV.
[0059] Here, the inflection point refers to the point where the first concentration gradient section switches to the second concentration gradient section.
[0060] On the assumption that the total amount of cobalt in the lithium composite oxide is the same, when the inflection point defined above exists at a position where the acceleration voltage is less than 7.5 kV, the point where the first concentration gradient section switches to the second concentration gradient section exists too close to the outermost periphery of the lithium composite oxide, making it difficult to sufficiently prevent particle damage such as the occurrence of cracks inside the lithium composite oxide, the collapse of the crystal structure, or a change in the crystal structure (phase transition).
[0061] On the other hand, under the assumption that the total amount of cobalt in the lithium composite oxide is the same, when the inflection point defined above exists at a position where the acceleration voltage exceeds 12.5 kV, the point where the first concentration gradient section switches to the second concentration gradient section is too far away from the outermost periphery of the lithium composite oxide, making it difficult to sufficiently prevent particle damage such as the occurrence of cracks on the surface of the lithium composite oxide, the collapse of the crystal structure, or a change in the crystal structure (phase transition).
[0062] The lithium composite oxide defined in the present application is represented by Chemical Formula 1 below.
[0063] [C1] Li w Ni 1-(x+y+z+z’) Co x M1 y M2 z B z’ O2
[0064] (where: M1 is at least one selected from Mn and Al; M2 is at least one selected from P, Sr, Ba, Ti, Zr, Mn, Al, W, Ce, Hf, Ta, Cr, F, Mg, Cr, V, Fe, Zn, Si, Y, Ga, Sn, Mo, Ge, Nd, Gd, and Cu; M1 and M2 are different from each other, 0.5≦w≦1.5, 0≦x≦0.50, 0≦y≦0.20, 0≦z≦0.20, 0≦z'≦0.20.
[0065] The lithium composite oxide may be a high-Ni type lithium composite oxide in which the concentrations (mol %) of Ni, Co, M1, M2 and B in Chemical Formula 1 satisfy the following Relational Formula 1.
[0066] [Equation 1] i / (Ni+Co+M1+M2+B)≧80.0
[0067] The lithium composite oxide may be a high-Ni / low-Co type lithium composite oxide in which the concentrations (mol %) of Ni, Co, M1, M2 and B in Chemical Formula 1 satisfy the Relational Formula 1, and the Co content is 10 mol % or less, preferably 5 mol % or less.
[0068] That is, in the lithium composite oxide, the concentrations (mol %) of Ni, Co, M1, M2 and B in Chemical formula 1 can satisfy the following relational formula 2.
[0069] [Equation 2] Co / (Ni+Co+M1+M2+B)≦5.0
[0070] It is generally known that in lithium composite oxides containing at least nickel and cobalt, the structural instability of the lithium composite oxide due to Li / Ni cation mixing occurs as the Ni content increases. It has also been reported that in lithium composite oxides containing at least Ni and Co, the initial overpotential (resistance) increases as the Co content decreases, which inevitably leads to a decrease in rate characteristics.
[0071] However, the lithium composite oxide included in the cathode active material according to an embodiment of the present invention has a concentration gradient in which the cobalt concentration exhibits at least a different gradient from the surface portion to the center portion of the lithium composite oxide, thereby mitigating and / or preventing the structural instability and the deterioration of the rate characteristics of the high-Ni type or high-Ni / low-Co type lithium composite oxide.
[0072] On the other hand, the lithium composite oxide contained in the positive electrode active material defined in the present application may be a secondary particle including at least one primary particle.
[0073] Here, "secondary particles containing at least one primary particle" should be interpreted as including both "particles formed by agglomeration of multiple primary particles" and "non-agglomerated particles containing a single primary particle."
[0074] The primary particles and the secondary particles may each independently be rod-shaped, elliptical and / or irregular.
[0075] When the average major axis length is used as an index showing the size of the primary particles and the secondary particles, the average major axis length of the primary particles constituting the lithium composite oxide may be 0.1 μm to 5 μm, and the average major axis length of the secondary particles may be 1 μm to 30 μm. The average major axis length of the secondary particles may vary depending on the number of the primary particles constituting the secondary particles, and the positive electrode active material may contain particles having various average major axis lengths.
[0076] When the lithium composite oxide is "non-aggregated particles including a single primary particle" or "particles formed by agglomeration of a relatively small number of primary particles," the size (average particle size) of the primary particles contained in the "non-aggregated particles including a single primary particle" or "particles formed by agglomeration of a relatively small number of primary particles" may be larger than the primary particles (average particle size) contained in the "secondary particles formed by agglomeration of tens to hundreds or more primary particles."
[0077] Thus, lithium composite oxides that are "non-aggregated particles containing a single primary particle" or "particles formed by aggregating a relatively small number of primary particles" generally require stronger heat treatment conditions (high heat treatment temperature / long heat treatment time) than those that are used to produce "secondary particles formed by aggregating tens to hundreds or more primary particles." It is generally known that when heat treatment is performed for a long time at a temperature close to 1,000°C, particle growth (crystal growth) is promoted, the size of the single particles increases, and a positive electrode active material with a low degree of particle aggregation is obtained.
[0078] For example, when the lithium composite oxide is "non-aggregated particles including a single primary particle" or "particles formed by aggregating a relatively small number of primary particles", the primary particles may have an average major axis length in the range of 0.5 μm to 20 μm. On the other hand, when the lithium composite oxide is "particles formed by aggregating a plurality of (tens to hundreds or more) primary particles", the primary particles may have an average major axis length in the range of 0.1 μm to 5 μm.
[0079] The primary particle may also include at least one crystallite, i.e., the primary particle may be constituted as a single crystallite, or may exist as a particle including multiple crystallites.
[0080] In one embodiment, the lithium composite oxide is a secondary particle formed by agglomeration of a plurality of primary particles, and the cobalt in the secondary particles may have a concentration gradient that decreases from the surface portion to the center portion of the secondary particles.
[0081] In this case, the concentration gradient of cobalt formed within the secondary particles has at least different slopes, and the signs of the different slopes are the same.
[0082] In addition, during an EP-EDS (Energy Profiling-Energy Dispersive X-Ray Spectroscopy) analysis in which an electron beam is irradiated onto the surface of the secondary particles at an accelerating voltage that increases from 1 kV to 30 kV to measure a cumulative concentration of cobalt from the surface of the secondary particles to a depth penetrated by the electron beam, an inflection point at which the slope of the concentration gradient of cobalt in the secondary particles changes may be present within a region in which the accelerating voltage is 7.5 kV to 12.5 kV.
[0083] As described above, the inflection point refers to a point within the second particle where the first concentration gradient section switches to the second concentration gradient section.
[0084] In this case, the position of the inflection point may be determined as a position where the slope of the concentration gradient of the cobalt in the secondary particle changes suddenly, or may be determined as a position where an arbitrary acceleration voltage penetrates during EP-EDS analysis.
[0085] For example, the region of the acceleration voltage of 1 kV to 10 kV is defined as the first concentration gradient section, and the gradient of the concentration gradient of the cobalt in the lithium composite oxide in the first concentration gradient section is referred to as s1. Also, the region of the acceleration voltage of 10 kV to 30 kV is defined as the second concentration gradient section, and the gradient of the concentration gradient of the cobalt in the lithium composite oxide in the second concentration gradient section is referred to as s2. Of course, there may be an additional concentration gradient section inside the second concentration gradient section, but the particle stability of the lithium composite oxide intended in the present application can be sufficiently improved through the gradient of the concentration gradient of the cobalt in the first concentration gradient section and the gradient of the concentration gradient section of the cobalt in the second concentration gradient section.
[0086] A gradient s1 of the concentration gradient of the cobalt in the lithium composite oxide in the first concentration gradient section can satisfy the following formula 1.
[0087] [Formula 1] 2.0≦s1≦3.6
[0088] On the assumption that the total amount of cobalt in the lithium composite oxide is the same, the slope s1 of the concentration gradient in the first concentration gradient section being greater than 3.6 may mean that the point where the first concentration gradient section switches to the second concentration gradient section is too close to the outermost periphery of the lithium composite oxide, making it difficult to sufficiently prevent particle damage such as the occurrence of cracks inside the lithium composite oxide, the collapse of the crystal structure, or a change in the crystal structure (phase transition).
[0089] On the other hand, under the assumption that the total amount of cobalt in the lithium composite oxide is the same, the slope s1 of the concentration gradient in the first concentration gradient section being less than 2.0 may mean that the point where the first concentration gradient section switches to the second concentration gradient section is too far away from the outermost periphery of the lithium composite oxide. In this case, the content of cobalt in the surface portion of the lithium composite oxide is reduced, making it difficult to sufficiently prevent particle damage such as crack generation, collapse of the crystal structure, or change in the crystal structure (phase transition) in the surface portion of the lithium composite oxide.
[0090] Moreover, a gradient s2 of the concentration gradient of the cobalt in the lithium composite oxide in the second concentration gradient section can satisfy the following formula 2.
[0091] [Formula 2] 0.2≦s2≦0.7
[0092] On the assumption that the total amount of cobalt in the lithium composite oxide is the same, the slope s2 of the concentration gradient in the second concentration gradient section being greater than 0.7 may mean that the decrease in the cobalt concentration in the second concentration gradient section is excessively large. In this case, it is difficult to sufficiently prevent particle damage such as crack generation, collapse of the crystal structure, or change in the crystal structure (phase transition) inside the lithium composite oxide (inside the second concentration gradient section).
[0093] On the other hand, under the assumption that the total amount of cobalt in the lithium composite oxide is the same, the slope s2 of the concentration gradient in the second concentration gradient section being less than 0.2 may mean that the decrease in the cobalt concentration in the second concentration gradient section is too small. In this case, the content of cobalt in the surface region and adjacent region of the lithium composite oxide is reduced, making it difficult to sufficiently prevent particle damage such as crack generation, collapse of the crystal structure, or change in the crystal structure (phase transition) in the surface region and adjacent region of the lithium composite oxide.
[0094] In addition, in relation to the particle stability of the lithium composite oxide, it was confirmed that there is a predetermined correlation between the gradient s1 of the concentration gradient of the cobalt in the lithium composite oxide in the first concentration gradient section and the slope s2 of the concentration gradient of the cobalt in the lithium composite oxide in the second concentration gradient section.
[0095] Specifically, when s1 and s2 satisfy the following formula 3, the particle stability can be improved not only in the first concentration gradient section and the second concentration gradient section of the lithium composite oxide but also in the central portion of the lithium composite oxide.
[0096] [Formula 3] 1.7≦s1-s2≦3.0
[0097] Furthermore, the lithium composite oxide may further include a coating layer covering at least a part of the interfaces between the primary particles and the surfaces of the secondary particles, and in this case, the coating layer may contain at least one, preferably at least two, kinds of metal oxides represented by the following Chemical Formula 2.
[0098] [Case 2] Li a M3 b O c
[0099] (where: M3 is at least one selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, B, P, Eu, Sm, W, Ce, V, Ba, Ta, Sn, Hf, Ce, Gd, and Nd; 0≦a≦10, 0≦b≦8, 2≦c≦13, except when a and b are both 0.
[0100] The coating layer may be in a form in which different metal oxides are simultaneously present in one layer, or in which the different metal oxides represented by Chemical Formula 2 are each present in a separate layer.
[0101] The metal oxide represented by Chemical Formula 2 may be in a state of being physically and / or chemically bonded to the primary particles and / or the secondary particles. In addition, the metal oxide may exist in a state of forming a solid solution with the primary particles and / or the secondary particles.
[0102] The metal oxide is an oxide of a composite of lithium and an element represented by M3, or an oxide of M3. The metal oxide is, for example, Li a W b O c , Li a Zr b O c , Li a Ti b O c , Li a Ni b O c , Li a B b O c , Li a Co b O c , Li a Al b O c , Co b O c , Al b O c , W b O c , Zr b O c , Ti b O cOr B b O c However, the above-mentioned examples are merely given for the sake of convenience to facilitate understanding, and the metal oxide defined in the present application is not limited to the above-mentioned examples.
[0103] The metal oxide may be an oxide in which lithium and at least two elements represented by M3 are combined, or may further include a metal oxide in which lithium and at least two elements represented by M3 are combined. The metal oxide in which lithium and at least two elements represented by M3 are combined may be, for example, Li a (W / Ti) b O c , Li a (W / Zr) b O c , Li a (W / Ti / Zr) b O c , Li a (W / Ti / B) b O c It may be, but is not necessarily limited to, the above.
[0104] The different concentration gradient patterns of cobalt in the lithium composite oxide included in the positive electrode active material according to the present application may be formed by the coating layer. That is, the different concentration gradient patterns of cobalt in the lithium composite oxide may be realized by the concentration of cobalt present in the primary particles and / or secondary particles and the concentration of cobalt present in the metal oxide present on the surfaces of the primary particles and / or secondary particles.
[0105] In this way, the lithium composite oxide exhibiting different concentration gradient patterns can improve particle stability at the surface and center portions, and can also improve the movement of ions and electrons at the center portion, thereby contributing to improving the efficiency characteristics of lithium secondary batteries.
[0106] In another embodiment, the positive electrode active material may be a bimodal positive electrode active material including a first lithium composite oxide having small particles and a second lithium composite oxide having large particles, the first lithium composite oxide and the second lithium composite oxide being in accordance with the definition of the lithium composite oxide described above.
[0107] In the present application, the range of the average particle size (D50) of small particles and large particles is not particularly limited, but in order to distinguish whether any lithium composite oxide is small particles or large particles, the following reference range of the average particle size (D50) of small particles and large particles may be determined.
[0108] Small particles refer to lithium composite oxides having an average particle size (D50) of 7.0 μm or less, and large particles refer to lithium composite oxides having an average particle size (D50) of 7.0 μm or more. In this case, when the average particle size (D50) of the small particles is 7.0 μm, the average particle size (D50) of the large particles is larger than 7.0 μm. There is no upper limit to the average particle size D50 of the large particles, but for example, the large particles may have an average particle size of 7.0 to 30.0 μm.
[0109] In the bimodal cathode active material according to various embodiments of the present invention, the first lithium composite oxide and the second lithium composite oxide having the average particle size (D50) defined above may be present in a mixed state in a weight ratio of 5:95 to 50:50.
[0110] In this case, the first lithium composite oxide may be present in a form in which it fills gaps between the second lithium composite oxide, or it may be attached to the surface of the second lithium composite oxide, or it may be present in a form in which the first lithium composite oxides are aggregated together.
[0111] When the ratio of the first lithium composite oxide to the second lithium composite oxide in the positive electrode active material is excessively high or low, the press density of the positive electrode active material is reduced, and the effect of improving the energy density per unit volume of the positive electrode active material becomes insignificant.
[0112] Lithium secondary battery According to yet another aspect of the present invention, a positive electrode may be provided, the positive electrode active material layer including a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector. Here, the positive electrode active material layer may include a positive electrode active material according to various embodiments of the present invention. Therefore, since the positive electrode active material is as described above, detailed description will be omitted for convenience, and only the remaining components not described above will be described below.
[0113] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may usually have a thickness of 3 to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0114] The positive electrode active material layer may be prepared by coating a positive electrode slurry composition containing the positive electrode active material, a conductive material, and optionally a binder, on the positive electrode current collector.
[0115] At this time, the positive electrode active material may be included in an amount of 80 to 99 wt%, more specifically, 85 to 98.5 wt%, based on the total weight of the positive electrode active material layer. When included in this content range, excellent capacity characteristics can be exhibited, but the amount is not necessarily limited thereto.
[0116] The conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery that is constructed. Specific examples include graphite such as natural graphite and artificial graphite, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, summer black, carbon-based materials such as carbon fibers, metal powders or metal fibers such as copper, nickel, aluminum, and silver, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, and conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in combination. The conductive material may be contained in an amount of 0.1 to 15% by weight based on the total weight of the positive electrode active material layer.
[0117] The binder serves to improve the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, and among these, one type alone or a mixture of two or more types may be used. The binder may be included in an amount of 0.1 to 15% by weight based on the total weight of the positive electrode active material layer.
[0118] The positive electrode may be manufactured by a typical method for manufacturing a positive electrode, except for using the positive electrode active material. Specifically, the positive electrode may be manufactured by dissolving or dispersing the positive electrode active material and, optionally, a binder and a conductive material in a solvent to prepare a positive electrode slurry composition, which is then coated on a positive electrode current collector, followed by drying and rolling.
[0119] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, and to provide a viscosity that allows excellent thickness uniformity when applied to manufacture a positive electrode, taking into consideration the coating thickness of the slurry and the production yield.
[0120] In another embodiment, the positive electrode may be manufactured by casting the positive electrode slurry composition on a separate support, peeling the positive electrode slurry composition from the support, and laminating the resulting film on a positive electrode current collector.
[0121] According to yet another aspect of the present invention, there may be provided an electrochemical device including the above-mentioned positive electrode. The electrochemical device may be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.
[0122] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode facing the positive electrode, and a separator and an electrolyte interposed between the positive electrode and the negative electrode. Here, since the positive electrode is as described above, a detailed description thereof will be omitted for convenience, and only the remaining components not described above will be described in detail below.
[0123] The lithium secondary battery may optionally further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.
[0124] The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.
[0125] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may generally have a thickness of 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.
[0126] The negative electrode active material layer may be prepared by coating a negative electrode slurry composition containing the negative electrode active material, a conductive material, and optionally a binder, on the negative electrode current collector.
[0127] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon, metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys, and SiO β(0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide, or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites and Sn-C composites, may be used. A metallic lithium thin film may be used as the negative electrode active material. Low-crystalline carbon and high-crystalline carbon may both be used as the carbon material. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, flake-like, spherical or fibrous natural graphite or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.
[0128] The negative electrode active material may be included in an amount of 80 to 99 wt % based on the total weight of the negative electrode active material layer.
[0129] The binder is a component that aids in bonding between the conductive material, the active material, and the current collector, and may be added in an amount of usually 0.1 to 10 wt% based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.
[0130] The conductive material may be added as a component for further improving the conductivity of the negative electrode active material in an amount of 10% by weight or less, preferably 5% by weight or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it has conductivity without inducing a chemical change in the battery, and may be, for example, graphite such as natural graphite or artificial graphite, carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black, conductive fibers such as carbon fibers or metal fibers, metal powders such as carbon fluoride, aluminum, or nickel powder, conductive whiskey such as zinc oxide or potassium titanate, conductive metal oxides such as titanium oxide, or conductive materials such as polyphenylene derivatives.
[0131] In one embodiment, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent on a negative electrode current collector and drying the coating. Alternatively, the negative electrode slurry composition may be cast on a separate support, and a film obtained by peeling the negative electrode slurry composition from the support may be laminated on the negative electrode current collector.
[0132] In another embodiment, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent on a negative electrode current collector and drying the coating, or by casting the negative electrode slurry composition on a separate support, peeling the negative electrode slurry composition from the support, and laminating the resulting film on the negative electrode current collector.
[0133] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode to provide a passage for lithium ions to move. Any separator generally used in lithium secondary batteries may be used without any particular limitation. In particular, it is preferable that the separator has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high-melting point glass fiber, a polyethylene terephthalate fiber, or the like, may be used. In addition, in order to ensure heat resistance or mechanical strength, a separator coated with a ceramic component or a polymer material may be used, and may be selectively used as a single-layer or multi-layer structure.
[0134] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.
[0135] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0136] The organic solvent may be used without any particular limitation as long as it serves as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone, an ether solvent such as dibutyl ether or tetrahydrofuran, a ketone solvent such as cyclohexanone, an aromatic hydrocarbon solvent such as benzene or fluorobenzene, dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of the solvents that may be used include carbonate-based solvents such as ethylene carbonate (PC), alcohol-based solvents such as ethyl alcohol and isopropyl alcohol, nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can improve the charge / discharge performance of a battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred. In this case, the performance of the electrolyte may be excellent if the cyclic carbonate and the chain carbonate are mixed at a volume ratio of about 1:1 to about 1:9.
[0137] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3), LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt is preferably used within a range of 0.1 to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, so that excellent electrolyte performance can be exhibited and lithium ions can be effectively transferred.
[0138] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in battery capacity, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 to 5% by weight based on the total weight of the electrolyte.
[0139] As described above, the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics and life characteristics, and is therefore useful in the fields of portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).
[0140] The external shape of the lithium secondary battery according to the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, etc. Furthermore, the lithium secondary battery can be used not only as a battery cell used as a power source for a small device, but also preferably as a unit battery for a medium- to large-sized battery module including a plurality of battery cells.
[0141] According to yet another aspect of the present invention, there may be provided a battery module including the lithium secondary battery as a unit cell and / or a battery pack including the same.
[0142] The battery module or the battery pack can be used as a power source for one or more medium- to large-sized devices, such as a power tool, an electric vehicle (Electric Vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV), or a power storage system.
[0143] The present invention will be described in more detail below with reference to examples. However, these examples are for the purpose of illustrating the present invention, and the scope of the present invention is not to be construed as being limited by these examples.
[0144] Production Example 1. Production of positive electrode active material (1) Example 1 (a) NiCoAl(OH)2 hydroxide precursor (Ni:Co:Al=95:4:1 (at%)) was synthesized by a known co-precipitation method using nickel sulfate, cobalt sulfate, and aluminum sulfate. The synthesized hydroxide precursor was heated to 400°C at 2°C per minute and calcined at 400°C for 6 hours to convert it to an oxide precursor.
[0145] (b) The oxide precursor prepared in step (a) was mixed with LiOH (Li / (Ni+Co+Al) molar ratio=1.05), and the mixture was heated to 800°C at 2°C per minute in a sintering furnace while maintaining an O2 atmosphere, and then heat-treated at 800°C for 12 hours to obtain a lithium composite oxide.
[0146] (c) A 3.0 mol% aqueous solution of cobalt sulfate based on the concentration of the transition metal in the lithium composite oxide was prepared and added to the lithium composite oxide while stirring for 1 hour to produce a mixture. After dehydrating the mixture, it was dried at 120°C for 12 hours to produce a dried product.
[0147] (d) After mixing the dried product with B2O3 (B / (Ni+Co+Al)mol%=0.3), the mixture was placed in a sintering furnace, the O2 atmosphere was maintained, the temperature was raised to 700°C at 2°C per minute, and the mixture was heat-treated at 700°C for 12 hours to obtain Li1Ni 0.9179 Co 0.0691 Al 0.0100 B 0.0030 A lithium composite oxide having a composition of O2 was obtained. The composition of the lithium composite oxide was confirmed by ICP analysis.
[0148] (2) Example 2 (a) NiCoAl(OH)2 hydroxide precursor (Ni:Co:Al=95:4:1 (at%)) was synthesized by a known co-precipitation method using nickel sulfate, cobalt sulfate, and aluminum sulfate. The synthesized hydroxide precursor was heated to 400°C at 2°C per minute and calcined at 400°C for 6 hours to convert it to an oxide precursor.
[0149] (b) The oxide precursor prepared in step (a) was mixed with LiOH (Li / (Ni+Co+Al) molar ratio=1.05) and B2O3 (Li / (Ni+Co+Al) mol%=0.2), and the mixture was heated to 800°C at a rate of 2°C per minute in a sintering furnace while maintaining an O2 atmosphere, and then heat-treated at 800°C for 12 hours to obtain a lithium composite oxide.
[0150] (c) A 3.0 mol% aqueous solution of cobalt sulfate based on the concentration of the transition metal in the lithium composite oxide was prepared and added to the lithium composite oxide while stirring for 1 hour to produce a mixture. After dehydrating the mixture, it was dried at 120°C for 12 hours to produce a dried product.
[0151] (d) After mixing the dried product with B2O3 (B / (Ni+Co+Al) mol%=0.3), the mixture was placed in a sintering furnace, the O2 atmosphere was maintained, the temperature was raised by 2°C per minute to 700°C, and the mixture was heat-treated at 700°C for 12 hours to produce Li1Ni 0.9161 Co 0.0689 Al 0.0100 B 0.0050 A lithium composite oxide having a composition of O2 was obtained. The composition of the lithium composite oxide was confirmed by ICP analysis.
[0152] (3) Example 3 In step (d), the dried product was mixed with B2O3 (B / (Ni+Co+Al) mol%=0.5) and then heat-treated to obtain a lithium composite oxide in the same manner as in Example 1. As a result of ICP analysis, the obtained lithium composite oxide was Li1Ni 0.9161 Co 0.0689 Al 0.0100 B 0.0050 The composition of the lithium composite oxide was confirmed through ICP analysis.
[0153] (4) Example 4 A lithium composite oxide was obtained in the same manner as in Example 3, except that in step (d), the dried product was mixed with B2O3 (B / (Ni+Co+Al) mol%=0.3) and ZrO2 (Zr / (Ni+Co+Al) mol%=0.2) and then heat-treated. As a result of ICP analysis, the obtained lithium composite oxide was Li1Ni 0.9161 Co 0.0689 Al 0.010 B 0.0050 The composition of the lithium composite oxide was confirmed through ICP analysis.
[0154] (5) Example 5 A lithium composite oxide was obtained in the same manner as in Example 1, except that in step (b), the dried product was mixed with B2O3 (B / (Ni+Co+Al) mol%=0.3) and TiO2 (Ti / (Ni+Co+Al) mol%=0.2) and then calcined. As a result of ICP analysis, the obtained lithium composite oxide was Li1Ni 0.9161 Co 0.0689 Al 0.010 B 0.0030 Ti 0.0020 The composition of the lithium composite oxide was confirmed through ICP analysis.
[0155] (6) Example 6 A lithium composite oxide was obtained in the same manner as in Example 1, except that in step (b), the dried product was mixed with B2O3 (B / (Ni+Co+Al) mol%=0.3) and MgO (Mg / (Ni+Co+Al) mol%=0.2) and then calcined. As a result of ICP analysis, the obtained lithium composite oxide was Li1Ni 0.9161 Co 0.0689 Al 0.010 B 0.0030 Mg 0.0020 The composition of the lithium composite oxide was confirmed through ICP analysis.
[0156] (7) Comparative Example 1 (a) NiCoAl(OH)2 hydroxide precursor (Ni:Co:Al=95:4:1 (at%)) was synthesized by a known co-precipitation method using nickel sulfate, cobalt sulfate, and aluminum sulfate. The synthesized hydroxide precursor was heated to 400°C at 2°C per minute and calcined at 400°C for 6 hours to convert it to an oxide precursor.
[0157] (b) The oxide precursor prepared in step (a) was mixed with LiOH (Li / (Ni+Co+Al) molar ratio=1.05) and B2O3 (B / (Ni+Co+Al) mol%=0.3), and the mixture was heated to 800°C at a rate of 2°C per minute in a sintering furnace while maintaining an O2 atmosphere, and then heat-treated at 800°C for 12 hours to obtain a lithium composite oxide.
[0158] (c) A 3.0 mol% aqueous solution of cobalt sulfate based on the concentration of the transition metal in the lithium composite oxide was prepared and added to the lithium composite oxide while stirring for 1 hour to produce a mixture. After dehydrating the mixture, it was dried at 120°C for 12 hours to produce a dried product.
[0159] (d) The dried product was placed in a sintering furnace in an O2 atmosphere, heated to 700°C at a rate of 2°C per minute, and heat-treated at 700°C for 12 hours to obtain Li1Ni 0.9179 Co 0.0691 Al 0.0100 B 0.0030 A lithium composite oxide having a composition of O2 was obtained. The composition of the lithium composite oxide was confirmed by ICP analysis.
[0160] (8) Comparative Example 2 In step (d), the dried product was mixed with B2O3 (B / (Ni+Co+Al) mol%=0.8) and then calcined to obtain a lithium composite oxide in the same manner as in Example 2. ICP analysis showed that the obtained lithium composite oxide was Li1Ni 0.9113 Co 0.0687 Al 0.0100 B 0.0100 The composition of the lithium composite oxide was confirmed through ICP analysis.
[0161] (9) Comparative Example 3 In step (d), the dried product was mixed with B2O3 (B / (Ni+Co+Al) mol%=1.0) and then calcined to obtain a lithium composite oxide in the same manner as in Example 1. As a result of ICP analysis, the obtained lithium composite oxide was Li1Ni 0.9113 Co 0.0687 Al0.0100 B 0.0100 The composition of the lithium composite oxide was confirmed through ICP analysis.
[0162] (10) Comparative Example 4 (a) NiCoAl(OH)2 hydroxide precursor (Ni:Co:Al=95:4:1 (at%)) was synthesized by a known co-precipitation method using nickel sulfate, cobalt sulfate, and aluminum sulfate. The synthesized hydroxide precursor was heated to 400°C at 2°C per minute and calcined at 400°C for 6 hours to convert it to an oxide precursor.
[0163] (b) The oxide precursor prepared in step (a) was mixed with LiOH (Li / (Ni+Co+Al) molar ratio=1.05), and the mixture was heated to 800°C at 2°C per minute in a sintering furnace while maintaining an O2 atmosphere, and then heat-treated at 800°C for 12 hours to obtain a lithium composite oxide.
[0164] (c) The lithium composite oxide is placed in a sintering furnace in an O2 atmosphere, heated to 700°C at a rate of 2°C per minute, and heat-treated at 700°C for 12 hours to obtain Li1Ni 0.950 Co 0.040 Al 0.010 A lithium composite oxide having a composition of O2 was obtained. The composition of the lithium composite oxide was confirmed by ICP analysis.
[0165] Manufacturing Example 2. Manufacturing of lithium secondary batteries A positive electrode slurry was prepared by dispersing 92 wt% of the positive electrode active material prepared in Preparation Example 1, 4 wt% of artificial graphite, and 4 wt% of PVDF binder in 30 g of N-methyl-2-pyrrolidone (NMP). The positive electrode slurry was uniformly applied to a thin aluminum film having a thickness of 15 μm and dried in a vacuum at 135° C. to prepare a positive electrode for a lithium secondary battery.
[0166] A coin battery was fabricated using a lithium foil as a counter electrode for the positive electrode, a porous polyethylene film (Celgard 2300, thickness: 25 μm) as a separator, and an electrolyte solution of LiPF6 at a concentration of 1.15 M in a solvent of ethylene carbonate and ethyl methyl carbonate mixed in a volume ratio of 3:7.
[0167] Experimental Example 1: EP-EDS analysis of positive electrode active material An EP-EDS analysis was performed to measure the cobalt content in the lithium composite oxide contained in the positive electrode active material prepared according to Preparation Example 1. In the EP-EDS analysis, the lithium composite oxide contained in the positive electrode active material prepared according to Preparation Example 1 was selected, and the accelerating voltage of the electron beam irradiated to the surface of the selected lithium composite oxide was changed from 1 kV to 30 kV (1 kV, 3 kV, 5 kV, 7.5 kV, 10 kV, 12.5 kV, 15 kV, 22.5 kV, 30 kV) to analyze the cumulative concentration (at%) of cobalt up to a specific depth penetrated by the electron beam for each accelerating voltage.
[0168] The region where the acceleration voltage of the electron beam irradiated to the surface of the lithium composite oxide is from 1 kV to 10 kV is defined as a first concentration gradient section, and the region where the acceleration voltage is from 10 kV to 30 kV is defined as a second concentration gradient section. The gradient of the cobalt concentration gradient in the first concentration gradient section is defined as s1, and the gradient of the cobalt concentration gradient in the second concentration gradient section is defined as s2.
[0169] The slopes of the cobalt concentration gradient, s1 and s2, were calculated by taking the change in cobalt concentration (Δat%) on the y-axis and the change in EDS accelerating voltage (ΔkV%) on the x-axis, and were calculated as the average value obtained by adding up the slopes of each measurement region.
[0170] The EP-EDS analysis results for the lithium composite oxide contained in the positive electrode active material prepared in Preparation Example 1 are shown in Tables 1 and 2 below.
[0171] [Table 1]
[0172] [Table 2]
[0173] Referring to the results of Tables 1 and 2, a concentration gradient is formed in which the cobalt concentration decreases from the surface to the center of the lithium composite oxide contained in the positive electrode active materials according to Examples 1 to 6. At this time, it can be seen that there is a significant difference between the slopes of the concentration gradients when the acceleration voltage of the electron beam irradiated to the surface of the lithium composite oxide is in a range of 1 kV to 10 kV as a first concentration gradient section and when the acceleration voltage is in a range of 10 kV to 30 kV as a second concentration gradient section.
[0174] Meanwhile, in the case of the lithium composite oxide contained in the positive electrode active material according to Comparative Example 4, a concentration gradient is formed in which the cobalt concentration decreases from the surface toward the center. However, it can be confirmed that there is no significant difference between the slope of the concentration gradient in the first concentration gradient section in which the acceleration voltage of the electron beam irradiated to the surface of the lithium composite oxide is in the range from 1 kV to 10 kV and the slope of the concentration gradient in the second concentration gradient section in which the acceleration voltage is in the range from 10 kV to 30 kV.
[0175] Experimental Example 2: Evaluation of the electrochemical properties of a lithium secondary battery A charge / discharge experiment was performed on the lithium secondary battery (coin cell) manufactured in Manufacturing Example 2 using an electrochemical analyzer (Toyo, Toscat-3100) at 25° C., voltage range of 3.0 V to 4.25 V, and discharge rate of 0.2 C, to measure the charge and discharge capacities.
[0176] In addition, the same lithium secondary battery was charged / discharged 50 times at 25°C and 1C / 1C within a driving voltage range of 3.0V to 4.25V, and then the ratio of the discharge capacity at the 50th cycle to the initial capacity (cycle capacity retention) was measured.
[0177] The measurement results are shown in Table 3 below.
[0178] [Table 3]
[0179] Experimental Example 3. Evaluation of the stability of positive electrode active materials and lithium secondary batteries (1) Crack area of positive electrode active material after life The lithium secondary battery (coin cell) manufactured in Manufacturing Example 2 was charged / discharged 50 times at 25° C. and 1C / 1C within a driving voltage range of 3.0V to 4.25V, and then the positive electrode was separated. The positive electrode active material was recovered from the separated positive electrode, and a cross-sectional SEM image was taken.
[0180] In order to quantify (binarize) the crack area in the cross-sectional SEM image, the outline of multiple particles observed in the cross-sectional SEM image was set, and the dark areas within the outline were regarded as cracks. The ratio of the area of the dark areas to the total area within the outline was defined as the crack occurrence rate (%).
[0181] The crack occurrence rates measured by the above-mentioned method are shown in Table 4 below.
[0182] [Table 4]
[0183] Referring to the results in Table 4, it can be seen that the positive electrode active materials according to Examples 1 to 6 had a lower crack occurrence rate after the end of the life of the lithium secondary battery than the positive electrode active materials according to Comparative Examples 1 to 4.
[0184] (2) Measurement of gas generation rate of lithium secondary batteries The lithium secondary battery prepared according to Preparation Example 2 was charged to 4.25 V at a constant current of 0.2 C and then stored at 60° C. for 14 days, and the volume change of the lithium secondary battery due to gas generation in the lithium secondary battery was measured. The volume change measurement results are shown in Table 5 below.
[0185] [Table 5]
[0186] Repeated charging and discharging may cause cracks in the positive electrode active material, which may increase the possibility of a side reaction between the positive electrode active material and the electrolyte through the cracks, resulting in the generation of gas. Referring to the results in Table 6, it can be seen that the volume change of the lithium secondary batteries using the positive electrode active materials according to Examples 1 to 6 is smaller than the volume change of the lithium secondary batteries using the positive electrode active materials according to Comparative Examples 1 to 4.
Claims
1. A positive electrode active material comprising a lithium composite oxide containing at least nickel and cobalt, Cobalt in the lithium composite oxide has a concentration gradient that decreases from the surface portion to the center portion of the lithium composite oxide, the cobalt concentration gradient has at least different slopes, the signs of the different slopes being the same as each other; When an EP-EDS (Energy Profiling-Energy Dispersive X-Ray Spectroscopy) analysis is performed to measure a cumulative concentration of cobalt from the surface of the lithium composite oxide to a depth penetrated by the electron beam using an electron beam irradiated at an acceleration voltage increasing from 1 kV to 30 kV to the surface of the lithium composite oxide, an inflection point at which the slope of the concentration gradient of the cobalt in the lithium composite oxide changes is present within a region of an acceleration voltage of 7.5 kV to 12.5 kV, A positive electrode active material in which an average value of a gradient of the concentration of cobalt in the lithium composite oxide within a region where an acceleration voltage is 1 kV to 10 kV is s1 and an average value of a gradient of the concentration of cobalt in the lithium composite oxide within a region where an acceleration voltage is 10 kV to 30 kV is s2, and the s1 and s2 satisfy the following formula 3. [Formula 3] 1.7≦s1−s2≦3.0
2. 2. The positive electrode active material according to claim 1, wherein the absolute value of the gradient of the concentration of cobalt in the lithium composite oxide in a region where the acceleration voltage is 1 kV to 10 kV is greater than the absolute value of the gradient of the concentration of cobalt in the lithium composite oxide in a region where the acceleration voltage is 10 kV to 30 kV.
3. The lithium composite oxide is a secondary particle formed by agglomeration of a plurality of primary particles, Cobalt in the secondary particles has a concentration gradient that decreases from the surface portion to the center portion of the secondary particles, 2. The positive electrode active material of claim 1, wherein, in an energy profiling-energy dispersive X-ray spectroscopy (EP-EDS) analysis in which a cumulative concentration of cobalt from the surface of the secondary particles to a depth penetrated by the electron beam is measured using an electron beam irradiated to the surface of the secondary particles at an acceleration voltage that increases from 1 kV to 30 kV, an inflection point at which a gradient of the concentration of cobalt in the secondary particles changes is present within a region where the acceleration voltage is 7.5 kV to 12.5 kV.
4. When the average value of the gradient of the concentration of the cobalt in the lithium composite oxide in the region where the acceleration voltage is 10 kV to 30 kV is s2, The positive electrode active material according to claim 1 , wherein s2 satisfies the following formula 2: [Formula 2] 0.2≦s2≦0.7
5. The positive electrode active material according to claim 1 , wherein the lithium composite oxide is represented by the following Chemical Formula 1. [Chemical formula 1] Li w Ni 1-(x+y+z+z’) Co X M1 y M2 z B z’ O 2 (where: M1 is at least one selected from Mn and Al; M2 is at least one selected from P, Sr, Ba, Ti, Zr, Mn, Al, W, Ce, Hf, Ta, Cr, F, Mg, Cr, V, Fe, Zn, Si, Y, Ga, Sn, Mo, Ge, Nd, Gd, and Cu; M1 and M2 are different from each other, 0.5≦w≦1.5, 0≦x≦0.50, 0≦y≦0.20, 0≦z≦0.20, and 0≦z′≦0.20.)
6. The lithium composite oxide further includes a coating layer that covers at least a portion of the interfaces between the primary particles and the surfaces of the secondary particles, The positive electrode active material according to claim 3 , wherein the coating layer contains at least one metal oxide represented by the following formula 2: [Chemical 2] Li a M3 b O c (where: M3 is at least one selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, B, P, Eu, Sm, W, Ce, V, Ba, Ta, Sn, Hf, Ce, Gd, and Nd; 0≦a≦10, 0≦b≦8, 2≦c≦13, except when a and b are both 0.
7. The cathode active material of claim 6 , wherein the metal oxide comprises cobalt.
8. The positive electrode active material according to claim 3, wherein the primary particles have an average particle size of 0.1 μm to 5 μm.
9. The positive electrode active material according to claim 3, wherein the secondary particles have an average particle size of 1 μm to 30 μm.
10. A positive electrode active material comprising a lithium composite oxide containing at least nickel and cobalt, Cobalt in the lithium composite oxide has a concentration gradient that decreases from the surface portion to the center portion of the lithium composite oxide, the cobalt concentration gradient has at least different gradients, the signs of the different gradients being the same as each other; When an EP-EDS (Energy Profiling-Energy Dispersive X-Ray Spectroscopy) analysis is performed to measure a cumulative concentration of cobalt from the surface of the lithium composite oxide to a depth penetrated by the electron beam using an electron beam irradiated at an acceleration voltage increasing from 1 kV to 30 kV to the surface of the lithium composite oxide, an inflection point at which the slope of the concentration gradient of the cobalt in the lithium composite oxide changes is present within a region of an acceleration voltage of 7.5 kV to 12.5 kV, A positive electrode active material, wherein s2 is an average value of a gradient of the concentration of cobalt in the lithium composite oxide within a region where the acceleration voltage is 10 kV to 30 kV, and s2 satisfies the following formula 2: [Formula 2] 0.2≦s2≦0.7
Citation Information
Patent Citations
Positive electrode active material for secondary battery and secondary battery containing the same
JP2018532236A
Positive electrode active material precursor for secondary battery and positive electrode active material for secondary battery prepared by using the same
KR102081858B1
Cited By
Semiconductor device and method of manufacturing the same
CN122719102A